Agentic AI and the Future of Fashion: Autonomous Creativity and Intelligent Systems - Burnstine, Andrew (Archives of Business Research, 2025)
The fashion industry is undergoing a profound transformation driven by rapid advancements in artificial intelligence (AI). While generative AI has demonstrated its capabilities in content creation and design ideation, the emergence of agentic AI heralds a paradigm shift towards autonomous systems capable of sophisticated perception, decision-making, and action within complex and dynamic environments. Unlike traditional AI tools that require specific inputs and human oversight for each step, agentic AI possesses the capacity for continuous learning, goal-driven behavior, and intricate decision-making with minimal direct human intervention. This paper delves into the transformative potential of agentic AI across the fashion ecosystem, encompassing design innovation, on-demand and automated manufacturing processes, personalized retail experiences, and the optimization of sustainable supply chain management. Drawing upon state-of-the-art research, empirical data, and critical analyses of industry applications, we examine how agentic AI is poised to redefine creative processes, enhance operational efficiency, and contribute to environmental responsibility within the fashion sector. Furthermore, this study addresses critical ethical, practical, and socio-cultural considerations arising from the integration of agentic AI, such as algorithmic bias, explainability, intellectual property rights, and the evolving role of human designers in this evolving landscape. By synthesizing technological, operational, and socio-cultural perspectives, this research aims to provide a comprehensive and forward-looking framework for understanding the multifaceted impact of agentic AI and its potential to disrupt and fundamentally reimagine the future trajectory of the fashion industry.